Nicaraguan dances in time of crisis. 2019: one year after the citizen uprisings - Jarquín-Madriz, Lucía (2022)
The article presents an interpretation of the civic uprisings in Nicaragua that began on April 18, 2018, through dance. These actions are analyzed from five key moments developed from the perspective of Colectivo Sinergia as well as from the interpretation of the authors from the corporal expression in relation to the violent acts of the Nicaraguan government against people. To do this, a series of anonymous interviews with victims of this new reality are taken as input.